Modeling the variation trends of glacier systems - Z. Xie; X. Wang; Q. Li; S. Liao; Y. Dai (Лëд и снег, 2015)
The basic principles and methods for a functional glacier systems model are introduced and applied for glaciers of Northwest China. When running the model we assume that a glacier system is under steady state conditions in the initial year. The median size of a glacier system is used as representative for the system. The curve of glacier area distribution against elevation is used to compute the increase in equilibrium line altitude (ELA), and the annual glacier ablation is calculated using a global formula a = 1.33(9.66 + ts)².⁸⁵ [4, p. 96]. The net mass balance near the ELA under steady state conditions represents the net mass balance of the whole glacier system, and the time required for glacier runoff to return to the initial year level is calculated according to the law of glacier runoff variation, and used to calculate the variation of glacier area. The variation of glacier runoff is modeled according to ablation at the ELA, and the variation of glacier volume is modeled according to the absolute value of the mass balance. The observed changes in surveyed glaciers in China over recent decades were broadly consistent with predictions of the glacier system model. The model therefore offers a reliable method for the prediction of changes in glacier systems in response to changing climate.